2008
DOI: 10.2187/bss.22.8
|View full text |Cite
|
Sign up to set email alerts
|

Growth of terrestrial cyanobacterium, Nostoc sp., on Martian Regolith Simulant and its vacuum tolerance

Abstract: The growth of terrestrial cyanobacterium, Nostoc sp., on the Martian Regolith Simulant (MRS) and its vacuum tolerance were studied as one of our challenges in this century to inhabit Mars. The viability of the tested cyanobacteria was evaluated by microscopic observation after staining by fluorescein diacetate (FDA). The general terrestrial cyanobacterial lump collected from the ground showed a significantly high tolerance to a high vacuum environment (10 -5 Pa) for over one year. To scientifically elucidate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…I am grateful to Dr. Kaori Tomita-Yokotani, Dr. Seigo Sato of Tsukuba University, Dr. Masayuki Ohmori of Saitama University, Dr. Hirofumi Hashimoto and Dr. Masamichi Yamashita of JAXA, co-author of the original paper (Arai et al, 2008). I wish to thank Dr. Hiroshi Takeda …”
Section: Acknowledgementsmentioning
confidence: 97%
“…I am grateful to Dr. Kaori Tomita-Yokotani, Dr. Seigo Sato of Tsukuba University, Dr. Masayuki Ohmori of Saitama University, Dr. Hirofumi Hashimoto and Dr. Masamichi Yamashita of JAXA, co-author of the original paper (Arai et al, 2008). I wish to thank Dr. Hiroshi Takeda …”
Section: Acknowledgementsmentioning
confidence: 97%
“…Fluorescein diacetate (FDA) staining method (Jones and Senft, 1985;Mori et al, 2002;Arai et al, 2008) was used as the viability assay. One mg of dissolved FDA in 0.5 ml dimethylsulfoxide and 0.2 ml acetone, which was kept in a refrigerator as an FDA stock solution.…”
Section: The Viability Assaymentioning
confidence: 99%
“…HK-01 is one of the candidate species of terrestrial organisms for the introduction to Mars. Arai et al, (2008) reported that Nostoc sp. HK-01 could grow for a period of 140 days on Martian regolith simulant which does not include a carbon source or a nitrogen source.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations